Quercetin prevents docetaxel- induced testicular damage in rats - Altintas, R.; Ciftci, O.; Aydin, M.; Akpolat, N.; Oguz, F.; Beytur, A. (Wiley, 2015)
The protective effect of quercetin on docetaxel - an anticancer agent - induced testicular damage in rats was investigated. Thirty-two rats were randomly divided into four groups: group 1 - control, carrier solutions were given; group 2 - quarcetin 20mgkg(-1)day(-1) was given orally; group 3 - docetaxel 5mgkg(-1) was given intraperitoneally as single dose; group 4 - docetaxel and quarcetin were given together. The histopathological changes; the specific biochemical markers, including antioxidants; and the sperm characteristics were evaluated. Docetaxel caused a significant increase in TBARS level and a significant decrease in SOD, GPX, CAT and GSH levels in the testicular tissues compared with the control group, whereas quercetin led to a significant decrease in lipid peroxidation, which was caused by docetaxel, via reducing TBARS level and increasing the levels of SOD, CAT, GPX and GSH. In addition, after docetaxel administration, sperm motility, sperm concentration, testicular and epididymis weights were significantly decreased and abnormal sperm rate and histopathological changes were increased. However, these effects of docetaxel on sperm parameters, histological changes and the tissue weights were eliminated by quercetin treatment. Our results show that the administration of docetaxel induced the testicular damage (oxidative stress, testes tissue damage and sperm parameters), and quercetin prevented docetaxel-induced testicular damage in rats.
Keywords: Docetaxel; quercetin; rat; testicular damage